2014
DOI: 10.1186/s40200-014-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Do overweight students have lower academic performance than their classmates? A pilot cross sectional study in a middle school in Tehran

Abstract: BackgroundRecently the special attention is given to psychological aspects of childhood obesity in overweight and obese children. The present pilot study aims to investigate the association of obesity and lipid profile with school performance among Iranian students.Methods69 middle school male students between the ages of 12 to 14 in 2009–2010 were studied. BMI was considered as the obesity index. The students’ Grade Point Average (GPA) along with their scores in math, geometry, calculus, English and absent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Ten studies reported the statistical power of the analysis (54,56,58,60,65,66,69,71,74,77) Thirteen studies did not report any adjustment for potential confounding factors in their analysis (51,(56)(57)(58)60,61,63,68,73,76,79,80,81).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies reported the statistical power of the analysis (54,56,58,60,65,66,69,71,74,77) Thirteen studies did not report any adjustment for potential confounding factors in their analysis (51,(56)(57)(58)60,61,63,68,73,76,79,80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Eight (23.5%) studies did not report age (18,51,52,55,67,72,75,77). Studies were conducted in both genders, except Heshmat et al (73), which was conducted only in boys.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure ranges from 0 to 20, zero (0) being the lowest score and twenty (20) the highest score possible during an academic year according to the Portuguese School System. The validity and reliability of this measure has been evidenced in previous research [32] and is considered to be a robust school performance indicator [3].…”
Section: Academic Performancementioning
confidence: 99%